Bilateral facial palsy in an adult with chickenpox - Wong, Arthur; Kulasegarah, Jeyanthi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Chickenpox is a result of primary infection with varicella zoster virus. Isolated facial nerve palsy as a complication is rare, and here we report an extraordinary case of bilateral facial nerve palsy following chickenpox in an adult. A 55-year-old male presented to the emergency department with a day’s history of facial weakness. He had recently contracted chickenpox with an onset 16 days prior. Physical examination noted crusted vesicles all over the body and a bilateral facial palsy. There were no clinical signs of meningitis or cerebrovascular accident. He was managed with a short course of oral aciclovir and prednisolone and recovered fully after a month. Presentations of facial nerve palsy in chickenpox are rare and should be differentiated from Ramsay Hunt syndrome. Prognosis is relatively good with the majority of known cases seeing complete facial nerve recovery within 6 months.